2021
DOI: 10.1002/path.5778
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and methylation profiles of ectopic and eutopic endometrial tissues

Abstract: Adenomyosis and peritoneal endometriosis are common gynecologic lesions; they are characterized by aberrant locations of normal-appearing endometrium in myometrium and peritoneal surface, respectively. Both ectopic lesions are speculated to originate from uterine eutopic endometrium, which is composed of epithelium and stroma, but how these two different tissue types co-evolve in ectopic locations remains unclear. Here, we analyzed exome-wide mutations and global methylation in microdissected epithelium and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Implanted tissue proliferates at the affected sites, and eventually forms endometriotic lesions 3 . In support of this hypothesis, previous studies demonstrated that eutopic and ectopic endometrial tissue shared the same somatic gene variants 4 6 .…”
Section: Introductionmentioning
confidence: 58%
“…Implanted tissue proliferates at the affected sites, and eventually forms endometriotic lesions 3 . In support of this hypothesis, previous studies demonstrated that eutopic and ectopic endometrial tissue shared the same somatic gene variants 4 6 .…”
Section: Introductionmentioning
confidence: 58%
“…We used laser capture-microdissection to enrich the epithelial cells. Genomic DNA from individual specimen was extracted using the QIAmp formalin-fixed and paraffin-embedded DNA tissue kit (Qiagen, 56404), as previously reported 5,25 …”
Section: Methodsmentioning
confidence: 99%
“…Sequencing of epithelial and stromal cells in superficial and deep infiltrating lesions reveals characteristic somatic mutation profiles for each cell type derived from different clones suggesting each cell type is supported by their own stem/progenitor population ( 91 , 115 , 122 ). In support of this, both mesenchymal and epithelial stem/progenitor markers have been identified in ectopic lesions ( 25 , 29 , 29 , 76 , 123 125 ) ( Figure 3 ).…”
Section: Role Of Stem/progenitor Cells In Menstrual Disorders/regener...mentioning
confidence: 99%